"Cops and the Klan": police disavowal of risk and minimization of threat from the far-right - Castle, Taimi (Critical criminology, 2021)
Critical scholars argue that contemporary policing practices reproduce colonial logics through the maintenance of racial and economic inequality. In this article, I extend the framing of policing as a colonial project grounded in white supremacy to an analysis of police responses to white power mobilization during a heightened period of activity and violence (2015-2017). Borrowing from Perry and Scrivens (2018), I identify the two most common police responses - "disavowal of risk" and "minimization of threat" - in the official investigations into the deadly "Unite the Right" rally in Charlottesville, Virginia, on August 12, 2017. Based on an analysis of newspaper reports from across the United States during the two-year period since then, I found that local and federal law enforcement consistently trivialized the presence of white power groups in the community, elevated the potential threat from protestors, concentrated intelligence efforts on activists, and provided differential protection to white supremacists.